EFFICIENCY ANALYSIS OF GAS ENGINES MONOSPARK AND MULTISPARK IGNITION SYSTEMS - F. Abramchuk; O. Kabanov; D. Schvydkyi (Avtomobilʹnyj Transport (Harʹkov), 2014)
The results of comparison analysis of gas engine monospark and multispark ignition systems indices are presented. The results of these systems experimental investigation are given.